Incorporating palliative radiotherapy education into hospice and palliative medicine fellowship training: a feasibility study - Martin, Emily J.; Nalawade, Vinit V.; Murphy, James D.; Jones, Joshua A. (Annals of Palliative Medicine; Vol 8, No 4 (September 27, 2019): Annals of Palliative Medicine, 2019)
Background: Insufficient knowledge of radiotherapy among hospice and palliative medicine (HPM) physicians is a barrier to providing optimal palliative care. We sought to assess the impact of a palliative radiotherapy curriculum on the knowledge, attitudes, and practice behaviors of HPM fellows at a single institution. Methods: We implemented a palliative radiotherapy didactic course for HPM fellows. The course consisted of three one-hour lectures and a guided tour of the radiation oncology suite. Anonymous pre-post course surveys and a longitudinal assessment were used to assess curricular impact. Quantitative data analysis was performed using descriptive statistics with P values calculated using the Wilcoxon rank-sum test with continuity correction. Results: All eligible fellows completed the questionnaires. Prior to the course, all fellows agreed that possessing a working knowledge of palliative radiotherapy was important yet lacked confidence in this domain. Fellow-reported confidence increased significantly on post-course assessment, as did the mean score on objective knowledge assessment. This increased knowledge was retained on longitudinal evaluation at three months. The curricular intervention also impacted fellow-reported practice behaviors and attitudes. In the three months following the intervention, fellows were more likely to refer patients for palliative radiotherapy, more likely to collaborate with radiation oncologists, and more likely to view radiation oncologists as members of a comprehensive palliative care team. Conclusions: This feasibility study suggests that a brief curricular intervention can impact HPM fellows’ knowledge about, attitudes towards, and practice behaviors associated with the use of radiotherapy in the palliative management of advanced cancer patients.